School refusal and bullying in children with autism spectrum disorder - Marina Ochi; Kentaro Kawabe; Shinichiro Ochi; Tomoe Miyama; Fumie Horiuchi; Shu-ichi Ueno (BMC, 2020)
Abstract Background Few studies have explored school refusal in children with autism spectrum disorder (ASD), despite being considered a serious problem. One of the leading causes of school refusal is bullying, which is defined by the feelings of students who are bullied or not, and psychological suffering caused by a psychological or physical attack. This study investigated the characteristics of school refusal in children with ASD. Methods A total of 94 outpatients with school refusal and ASD and 143 outpatients with school refusal without ASD aged 6-18 years were included. Chi squared tests and Mann-Whitney tests were used to compare the characteristics of school refusal in children with and without ASD. Univariate and multivariate logistic regression analyses were performed to analyze the reasons for school refusal in children with ASD by sex. Results School refusal significantly occurred earlier in children with ASD than in those without. In addition, "bullying" was significantly associated with school refusal in both boys and girls with ASD. Conclusions These findings suggest that school refusal should be monitored early in children with ASD. The importance of recognizing bullying among children with ASD should be highlighted as an opportunity for early intervention.